Kinetics of naphthalene catalytic hydrogenation under high temperature and high pressure. (1st February 2020) - Bie, Shiquan; Jiang, Hongbo; Wang, Wei; Shu, Geping; Zhang, Xuwen; Wang, Hongxue; Gao, Shansong
Abstract: The catalytic hydrogenation reaction of naphthalene was carried out on the Ni–Mo/Al2 O3 catalyst by using a constant-temperature fixed-bed reactor with the temperature ranging from 315 °C to 400 °C and pressure ranging from 12 to 20 MPa. The model of naphthalene catalytic hydrogenation was proposed based on the Langmuir–Hinshelwood–Hougen–Watson competitive adsorption theory, and the model parameters were estimated. The results show that the hydrogenation reaction of naphthalene to tetralin is fast, and tetralin tends to form trans-decalin, while there is no direct conversion between trans-decalin and cis-decalin. The reaction activation energy of naphthalene to tetralin is the smallest.